Disitamab vedotin vs. gemcitabine-cisplatin regimen with immunotherapy: a comparative analysis of efficacy and safety in muscle-invasive bladder cancer - Zhang, Chuanao; Yu, Yanhang; Zhou, Qi; Ouyang, Jun; Zhang, Zhiyu (Frontiers in Immunology, 2025)
IntroductionMuscle-invasive bladder cancer (MIBC) is an aggressive bladder cancer characterized by invasion of the muscular bladder wall, often necessitating a multimodal treatment approach for optimal outcomes. This study aimed to compare the real-world efficacy and safety of disitamab vedotin (RC48), an antibody-drug conjugate (ADC), combined immunotherapy targeting programmed cell death protein-1 (PD-1), against the gemcitabine and cisplatin (GC) regimen with PD-1 immunotherapy in the treatment of MIBC.MethodsThis single-center, retrospective study was conducted at the First Affiliated Hospital of Soochow University and included 38 patients with MIBC treated with either RC48 plus immunotherapy or GC regimen plus immunotherapy, between January 2022 and December 2023. Patients were divided into two groups: the RC48 with immunotherapy (ADC + PD-1) group and the GC regimen with immunotherapy (GC + PD-1) group. Efficacy was evaluated based on their pathological complete response rates (PCRR) and pathological downstaging rates (PDR). Adverse events (AEs) were assessed to compare safety profiles.ResultsOf the 38 patients, 17 were in the ADC + PD-1 group and 21 were in the GC + PD-1 group. The PCRR was significantly higher in the ADC + PD-1 group (82.35%, 14/17) compared to the GC + PD-1 group (47.62%, 10/21; P = 0.043). The PDR was also higher in the ADC + PD-1 group (94.12%, 16/17) than in the GC + PD-1 group (80.95%, 17/21), although the difference was not statistically significant (P = 0.355). No serious allergic reactions or fatal AEs were reported in either group. No Grade 4 AEs were reported, while Grade 3 AEs occurred at a rate of 5.71% in the ADC + PD-1 group and 12.20% in the GC + PD-1 group (P = 0.260).ConclusionRC48 combined with immunotherapy demonstrated a significantly higher PCRR compared to the GC regimen with immunotherapy, while maintaining a comparable safety profile. These findings highlight the potential of RC48 combined with immunotherapy as an effective treatment option for MIBC in clinical practice.